Analisis Pengaruh Relationship Marketing, Kualitas Layanan, dan Penggunaan M-Banking Terhadap Loyalitas Nasabah PT Bank Syariah Indonesia (Studi Kasus pada Masyarakat di Kota Semarang) - Maryamah, Neni; Widowati, Mustika; Fajria, Rola Nurul (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2023)
This study aims to analyze the significance of the effect of relationship marketing, service quality, and the use of m-banking on customer loyalty at PT Bank Syariah Indonesia Tbk in Semarang City, either simultaneously or partially. The population in this study were all customers of PT Bank Syariah Indonesia Tbk in Semarang City. The sampling technique used was purposive sampling technique as many as 102 respondents. The data used in this study is primary data obtained through the distribution of questionnaires. The data analysis model used multiple linear regression analysis model. While the data analysis technique used the F statistical test, the coefficient of determination (R2) test, and the t statistic test which was processed using the SPSS 21.00 program.The results of the analysis and discussion show that relationship marketing, service quality, and the use of m-banking simultaneously have a significant effect on customer loyalty at PT Bank Syariah Indonesia Tbk in Semarang City. Partially, relationship marketing and service quality have a positive and significant effect. While the use of m-banking has a positive but not significant effect on customer loyalty at PT Bank Syariah Indonesia Tbk in Semarang City. Implementation of the results of this study PT Bank Syariah Indonesia Tbk needa to continue to strive to retain customers and increase customer loyalty. This can be realized in several ways, one of which is by optimizing relationship marketing and service quality for it”™s operations.